MODEL-MODEL PENDANAAN PENDIDIKAN DI INDONESIA - Fahrezi, Muhammad Adnan; Pandu Maulana, Muhamad; Nurwahid, Muhammad Salman; Aprilliantoni, Aprilliantoni (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Education finance has a critical role in guaranteeing the durability and calibre of the Indonesian educational system. The community, business sector, and government all contribute to a funding model that is thought to be the most effective approach to meet the needs for financing education. This article explores Indonesia's varied education funding schemes through an expert literature review. The primary pillar is still government support, which comes from the APBN and APBD, notwithstanding issues with uneven distribution that frequently arise. In addition to posing threats to the commercialisation of education, the private sector is crucial in completing the gaps left by the government. With community involvement in the form of donations and direct involvement at the school level, it is feasible to raise the sense of ownership and accountability in the management of education funds. A qualitative descriptive technique and literature review were used to perform this study. According to the study's findings, if different financing sources are combined and handled properly and responsibly, educational quality can be raised. Nonetheless, problems with opaque management and uneven finance must be addressed in order to build a more equitable and long-lasting educational system.